GeoGebra-supported Learning Kit for Teaching Area of Trapezoid Based on TPMK Framework - Triet, Le Viet Minh; Thanh, Ha Man (Unnes Journal of Mathematics Education, 2024)
The use of technology in education has expanded fast in the twenty-first century. The capacity to use technology in teaching materials has become a crucial talent for mathematics teachers, and it is a key topic in the current study. This is why, as a new teacher, you must be able to create ICT-based learning materials. This study aims to create an interactive mathematical learning media tool kit for teaching the area of trapezoid based on the TPMK framework and the GeoGebra dynamic mathematics program. This study was research and development (R&D) conducted with the Plomp development model. The designing stage is divided into two steps. In the first step, we created a model for developing a GeoGebra-supported teaching kit based on the TPMK framework originated from Shulman's (1986) stated in our theoretical foundation. In the second step, a concrete example of a task circumstance was created to demonstrate the model. This result shows that using GeoGebra dynamic mathematics software with a TPMK framework can help teachers explain abstract mathematics concepts to make them easier for students to understand.